Pengaruh Frekuensi Resonansiterhadappembangkitan Ozon Padadielectric Barrier Dischargeyang Terinduksi Magnet Dan Tanpa Magnet - Liho Dachanri Doly; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Ozone is a strong oxidizer consisting of oxygen which can replace chlorine so that it is used to treat wastewater, deodorizing, deinfecting, sterilizing medical devices and eliminating germs. Ozone can be generated by using ultraviolet radiation, optochemical reactions and dielectric barrier discharge (DHF). The most widely used ozone generation technology is dielectric barrier discharge.The power supply tools built are power supply as a PLN voltage rectifier, switch control circuit IC CD4047, push pull inverter circuit, parallel LC resonant circuit and flyback transformer as a voltage to voltage converter high.The resonant frequency of a parallel LC with a constant inductor (L) value of 100mH and a variation of the capacitor (C) value of 150nF, 470nF and 1F. This test also uses permanent magnets above and below the electrode with two conditions, namely attraction and without magnet. The test results show that the even distribution of plasma occured in dielectric barrier discharge (DHF) at a gap of 2mm air gap at a resonant frequency of 41 kHz in two magnetic conditions was attraction and without magnet. Furthermore, the greatest voltage seen occurs in the Ia model (resonant frequency 41 kHz magnetic attraction condition) compared to other conditions with a voltage value of 8.73kV. The highest ozone concentration in this study can be seen in the Ia model of all testing models. The ozone concentration of model IIc (503 Hz resonant frequency without magnetism) had the lowest ozone concentration of all models and conditions. Keyword: dielectric barrier discharge, inverter push pull parallel resonant, plasma, magnetic field, Ozone